Comparative effectiveness of improvement in pain and physical function for baricitinib versus adalimumab, tocilizumab, and tofacitinib monotherapies in rheumatoid arthritis patients who are naïve to treatment with biologic or conventional synthetic disease-modifying antirheumatic drugs: A matching-adjusted indirect comparison - Fautrel, B; Zhu, B; Taylor, PC; van de Laar, M; Emery, P; De Leonardis, F; Kannowski, CL; Nicolay, C; Kadziola, Z; De La Torre, I; Fleischmann, R (BMJ, 2020)
Objective: To compare improvement in pain and physical function for patients treated with baricitinib, adalimumab, tocilizumab and tofacitinib monotherapy from randomised, methotrexate (MTX)-controlled trials in conventional synthetic disease-modifying antirheumatic drugs (csDMARDs)/biologic (bDMARD)-naïve RA patients using matching-adjusted indirect comparisons (MAICs).